Bioinspired Synthesis of Nanoparticles and their Biomedical Potential: the Pakistan Experience: Bioinspired nanoparticle synthesis in Pakistan - Ullah, Sana; Ali, Muhammad; Din, Misbahud; Afridi, Shakeeb; Bashir, Samina; Shinwari, Zabta Khan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
Nanotechnology is an emerging field that play pivotal role in a wide range of scientific fields. Applications of nanotechnology have been successfully applied in healthcare, drug delivery, gene delivery, diagnostics, and energy sciences. Nanoparticle synthesis involves different methods like physical, chemical approaches and biological methods. The physical and chemical methods are associated with pitfalls as they pose potential threat to the environment; and hence ecofriendly routes of bioinspired nanoparticle synthesis are preferred. The biogenic synthesis of nanoparticles has attracted numerous researchers because of their potential advantages such as simplicity, safety, easy production, biocompatibility, and low production costs. Green synthesis of nanoparticles involves the mixing and processing of metal salts with plant/bacterial/fungal extracts. Secondary metabolites from biological sources have potentials for reducing the metal salt(s); herby synthesize respective nanoparticles. The current review is aimed to discuss reports and studies conducted in Pakistan that have used biological approach for nanoparticle synthesis, as well as their potential biological and pharmacological application/s. Future directions should involve market oriented approaches for the commercialization of nanoparticles-based products that can help in up-left of national economy.